ABO blood groups and thrombosis: a causal association, but is there value in screening?. (March 2011) - Clark, Peter; Wu, Olivia
ABO(H) antigens are expressed on red cells and on von Willebrand factor. An association between groups other than O and thrombosis exists: an effect that is predominantly mediated by von Willebrand factor. Overall, the risk of venous thrombosis associated with non-O has been estimated at 1.75-fold, with a higher risk (∼∼2.4-fold) in those with the least O(H) antigen (a combined group of A 1 A 1 /A 1 B/BB). Preliminary evidence also suggests that blood group may influence the venous thromboembolism risk associated with factor V Leiden. Overall, ABO(H) has a more modest effect on arterial disease, with a consistent effect observed in peripheral vascular disease and no influence evident with angina. A modest effect on myocardial infarction and stroke has been reported in some but not all studies. The potential mechanisms whereby blood group influences thrombosis, the limitations of current evidence and the current and future role of blood groups in identifying those at risk of arterial and venous disease is discussed.